Formation of insulin fragments by insulin‐degrading enzyme: the role of zinc(II) and cystine bridges†. (26th January 2013) - Bellia, Francesco; Pietropaolo, Adriana; Grasso, Giuseppe
<x xml:space="preserve">Abstract</x> Insulin is the hormone mainly involved in widespread diseases such as diabetes mellitus. It is widely recognized that metal ions such as zinc(II) as well as insulin degradation and insulin fragments are inexplicably linked to the hormone action. Insulin‐degrading enzyme (IDE) has been identified as the main factor of insulin degradation, but it is still unknown the exact way and location at which IDE action toward insulin occurs and how metal ions can modulate this interaction. Interestingly, some insulin fragments have different biological activity from the intact hormone, and it is not clear how they can be generated from insulin. In this work, the role of zinc(II) and cystine bridges in the degradation of insulin by IDE are investigated by high‐performance liquid chromatography‐mass spectrometry (HPLC‐MS), and the experimental conditions at which peculiar insulin fragments having biological activity are formed by the action of IDE are found and discussed. Docking simulations of IDE/insulin A and B chains are in good accordance with the insulin fragments detected by HPLC‐MS. Copyright © 2013 John Wiley & Sons, Ltd.